A single-domain expansin-like protein from Gloeophyllum trabeum able to cleave xylan - Ignacio Delgado Santamaría; Heidi Østby; Vincent G. H. Eijsink; Anikó Várnai (Proceedings of the National Academy of Sciences, 2026)
Expansin-related proteins (ERPs) are a broad group of plant cell wall–loosening proteins and are considered noncatalytic, as, to date, no cell wall–derived products have been observed as a result of catalysis, despite the presence of a domain that resembles the catalytic domains of GH45 endoglucanases. Here, we report catalytic activity for a single-domain ERP, Gt EXPN_133317, from the brown-rot fungus Gloeophyllum trabeum , which is highly expressed in the early phase of spruce colonization. We demonstrate enzyme-dependent formation of xylan-derived products, such as glucuronylated xylo-oligosaccharides, using high-performance anion exchange chromatography with pulsed amperometric detection. Structure-based multiple sequence alignment of ERPs with GH45 endoglucanases showed that, next to a single conserved aspartate (Asp87 in Gt EXPN_133317) present in all ERPs and GH45s, fungal ERPs contain a second conserved acidic residue (Asp25 in Gt EXPN_133317). Mutation of these two conserved amino acids, Asp87 and Asp25, led to a nearly complete loss of xylanolytic activity. While these findings do not exclude the possibility of a noncatalytic plant cell wall–loosening mechanism, they show that ERPs likely have other modes of action besides what the current paradigm states.